2010
DOI: 10.1172/jci37649
|View full text |Cite
|
Sign up to set email alerts
|

Role of chronic ryanodine receptor phosphorylation in heart failure and β-adrenergic receptor blockade in mice

Abstract: Increased sarcoplasmic reticulum (SR) Ca 2+ leak via the cardiac ryanodine receptor/calcium release channel (RyR2) is thought to play a role in heart failure (HF) progression. Inhibition of this leak is an emerging therapeutic strategy. To explore the role of chronic PKA phosphorylation of RyR2 in HF pathogenesis and treatment, we generated a knockin mouse with aspartic acid replacing serine 2808 (mice are referred to herein as RyR2-S2808D +/+ mice). This mutation mimics constitutive PKA hyperphosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
258
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(274 citation statements)
references
References 56 publications
(78 reference statements)
12
258
1
3
Order By: Relevance
“…Our finding that Zn 2ϩ reduces RyR S2808 phosphorylation is novel and potentially important in cardiomyocyte Ca 2ϩ regulation. Phosphorylation of RyR S2808 has been associated with increased RyR open probability and SR Ca 2ϩ leak due to dissociation of the stabilizing protein FKBP1B (16,29). Phosphorylation of RyR S2808 has been found especially high in the context of hyperglycemia and diabetes (30,38,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that Zn 2ϩ reduces RyR S2808 phosphorylation is novel and potentially important in cardiomyocyte Ca 2ϩ regulation. Phosphorylation of RyR S2808 has been associated with increased RyR open probability and SR Ca 2ϩ leak due to dissociation of the stabilizing protein FKBP1B (16,29). Phosphorylation of RyR S2808 has been found especially high in the context of hyperglycemia and diabetes (30,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of RyR S2808 has already been demonstrated to be associated with a high open probability of RyR and SR Ca 2ϩ leak (16,29). We were curious to test if Zn 2ϩ exposure could alter RyR S2808 phosphorylation and thus signal an effect on SR Ca 2ϩ leak, which could underlie diastolic function.…”
Section: Intracellular Zn 2ϩ Distribution In Cardiomyocytesmentioning
confidence: 99%
“…Further, S107 was recently shown to be effective at preventing ventricular arrhythmias in the mdx mouse model of muscular dystrophy [56] . Thus, 1,4-benzothiazepine derivatives JTV519 and S107 hold promise as RyR2-stabilizing molecules that could reduce the risk of arrhythmias [57] .…”
Section: Wwwchinapharcom Mccauley MD Et Almentioning
confidence: 99%
“…Shan et al [57] demonstrated that mice in which RyR2 was constitutively by PKA (RyR2-S2808D knock-in mice) exhibited an increased open probability, more calcium sparks, and increased SR Ca 2+ leak. Inhibition of PKA phosphorylation of RyR2 in RyR2-S2808A mice was shown to protect against catecholamineinduced ventricular arrhythmias [72] .…”
Section: Wwwnaturecom/aps Mccauley MD Et Almentioning
confidence: 99%
“…Yet, this is only partially the case, as shown by two studies from the Marks laboratory published in this issue of the JCI (25,26). The two papers report on two new mouse models: one in which the S2808 site was mutated to a non-phosphorylatable alanine (S2808A; ref.…”
Section: Evidence From Gene-targeted Phospho-mutant Ryr2 Mouse Modelsmentioning
confidence: 99%